Drosophila ABC transporter mutants white, brown and scarlet have altered contents and distribution of biogenic amines in the brain. - Borycz, J.; Borycz, J.A.; Kubów, A.; Lloyd, V.; Meinertzhagen, I.A. (Journal of Experimental Biology, 2008)
Monoamines such as dopamine, histamine and serotonin (5-HT) are widely distributed throughout the brain of the fruit fly Drosophila melanogaster, where many of their actions have been investigated. For example, histamine is released from photoreceptor synapses in the lamina neuropile of the visual system. Mutations of the genes white, an important eye pigmentation marker in fly genetics that encodes an ABC transporter, and its binding partner brown, cause neural phenotypes not readily reconciled solely with actions in eye pigmentation. We find that flies mutant for these genes, and another binding partner, scarlet, have about half the wild-type amount of histamine in the head, as well as reduced 5-HT and dopamine. These differences parallel reductions in immunoreactivity to the corresponding biogenic amines. They also correlate with the amine content of fractions after differential centrifugation of head homogenates. Thus, most of the amine is found in the vesicle-rich fraction of wild-type head homogenates, whereas it is found in the supernatant fractions from white, brown and scarlet flies. White co-expresses in lamina epithelial glia with Ebony, which conjugates histamine to beta-alanine. Histamine is then released when the conjugate is hydrolyzed in photoreceptors, by Tan. Mutant white ameliorates the effects of tan on head histamine whereas it exacerbates the effects of ebony. Our results are consistent with the proposal that histamine uptake by the epithelial glia may be white dependent. Behavioral abnormalities in white, brown and scarlet mutants could arise because aminergic neurons in the Drosophila brain have reduced amine for release.